METHODS FOR EFFECTIVE INFORMATION SEARCH,SELECTION,AND SYNTHESIS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2025)
In today's information-driven world, knowing how to search for, select, and synthesize information effectively is a crucial skill. Whether you are a student, researcher, or professional, the ability to gather,evaluate, and integrate information can significantly impact the quality of your work. This article outlines key methods and strategies for effective information search, selection,and synthesis,providing a framework for tackling information-heavy tasks.